Genome-wide association study of common bean (Phaseolus vulgaris L.) unveils novel loci governing root-to-seed zinc allocation - Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Sefa Ayten; Emre Aksoy; Sheikh Mansoor; E. M. B. M. Karunathilake; Yong Suk Chung; Faheem Shehzad Baloch (Scientific Reports)
Abstract Micronutrient malnutrition is a global health concern, highlighting the importance of essential micronutrients like zinc in human diet, and enhancing zinc concentration in staple crops like common beans is a promising strategy. In this study, we performed genome-wide association studies to identify genetic loci associated with Zn accumulation in a diverse panel of 177 Turkish common bean landraces and six commercial varieties. Field trials were conducted across two locations over two years to assess Zn concentration variation. The results revealed significant genetic variability, with Zn concentrations ranging from 11.6 to 105.3 mg/kg. Two significant marker-trait associations (MTAs) were identified on chromosomes Pv06 and Pv08, with loci linked to Zn translocation and brassinosteroid-mediated cell-wall remodeling. Candidate genes, Vacuolar Iron Transporter 1 (VIT1) and Wall-Associated Kinase-Like 4 (WAKL4), were implicated in Zn homeostasis and distribution. In silico transcriptomics analysis further validated the role of these genes under Zn-deficient conditions in Arabidopsis. Protein-protein interaction (PPI) network analysis identified key regulatory pathways, including ZIP transporters, heavy metal ATPases, and cell-wall modification enzymes. These findings provide valuable genetic insights for biofortification strategies, facilitating the development of Zn-enriched common bean cultivars to enhance nutritional security. The study underscores the potential of GWAS in identifying stable genetic markers for Zn biofortification, paving the way for future breeding efforts aimed at improving dietary Zn intake through staple crops.